PERBEDAAN SOSIAL EKONOMI DAN PENGETAHUAN GIZI IBU BALITA GIZI KURANG DAN GIZI NORMAL - Amelinda Calida Rahma; Siti Rahayu Nadhiroh (Universitas Airlangga, 2016)
There are many malnutrition problems in children under fi ve, especially in developing countries including Indonesia. One of factor affecting nutritional status is maternal nutrition knowledge that will imply in caring and feeding practice. Underweight is also affected by social economy factors such as family income, food expenditure, mother’s education and occupation. Therefore, the aim of this research was to analyze differences of social economy characteristic and maternal nutrition knowledge between under-fi ve children with underweight and normal nutritional status. Thisresearch was analytical-observational study with cross sectional design. Sample of this research was children aged 24–60 months that living in the working area of Sidotopo Public Health Centre. The number of sample was 19 children in each sub-population based on nutritional status. Data was collected through primary data collecting with direct interview and questionnaire. The result showed signifi cant difference of maternal nutrition knowledge between children with underweight and normal nutritional status (p = 0.004). There is no difference in social economy characteristic such as mother’s education (p = 0.189), mother’s occupation (p = 0.387), and family income (p = 0.189), and food expenditure (p = 0.515). Therefore, improving maternal nutrition knowledge and skills in local community or public health centre is necessary.Keywords: under-fi ve children, nutrition knowledge, nutritional status